PERAN KOMITE KEPERAWATAN TERHADAP PENINGKATAN MUTU PELAYANAN KEPERAWATAN - Alfianur; Pertiwiwati, Endang (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2018)
The position of the committee is in structure by the functional role of the organization whosepurpose was to collected, formulated, and communicated the opinions and ideas of the nurse.The purpose of the study was to analyzed the optimization of the role of nursing committeetoward the improvement of nursing service quality at the inpatient of Ulin Banjarmasin GeneralHospital. The research method was analytical descriptive with cross sectional approached. Thesamples in this research were all nurses who served in Inpatient at Ulin Banjarmasin generalhospital. The sample technique using Simple Random Sampling method. the number of sampleswere 92 people. The result of this research is Role of nursing committee in nursing service inRSUD ULIN Banjarmasin shows that 79 respondent or 85,9% is categorized its role optimally.Quality of Nursing Service in RSUD Banjarmasin as many as 70 respondents or 76.1%,categorized well. Result of analysis of relationship of optimization of nursing committee role toimprovement of quality of nursing service in ulin general hospital of Banjarmasin (p value =0,043 <0.05). Optimizing the role of the nursing committee can affect the quality improvement ofnursing services provided to the patient by maintaining the competence and accepting theresponsibilities ofevery action and decision made.